Prevalence and factors associated with depression and anxiety among students of backward community and minority girl’s hostels of Mysuru city - Y. S., Krishnaveni; B., Prakash; Kulkarni, Praveen; M. R., Narayanamurthy (International Journal Of Community Medicine And Public Health, 2018)
Background: Mental health is one of the major concerns among Non-communicable diseases with 10-20% of children and adolescents suffering mental disorders worldwide. If untreated, these conditions severely influence child’s development, education and their potential to live productive lives. This study is an effort to find out factors influencing mental health in hostel students, and its effects in their daily routine which will help hostel supervisors, parents and teachers to deal with students and help to achieve maximum progress in their academics. Methods: This is a Cross sectional study done among 353 students in BCM (backward community and minority) girls hostels of Mysuru. Students above 18 yrs and willing to participate in study are included and those suffering from acute illness/recent trauma /injury are excluded. Data collected using validated questionnaire (PHQ 9 for depression and GAD7 for anxiety). Results: Among 353 students included depression was observed in 245 (69.4%) of students and anxiety was found in 222 (62.8%) students. Depression and anxiety was associated with single parenting, socioeconomic class, masters degree courses, food habits, lifestyle and menstrual irregularities, multi logistic regression showed association of depression with premenstrual syndrome and anxiety with exercise, socioeconomic class, financial difficulties and premenstrual syndrome. Conclusions: Depression and anxiety were more prevalent in adolescent students and are associated with sedentary lifestyle, socioeconomic condition of students and reproductive health. Depression and Anxiety has impact on comfortable stay in hostel and relation with peers. These factors can be addressed to mitigate the effects.